The crucial role of blood VEGF kinetics in patients with locally advanced esophageal squamous cell carcinoma receiving curative concurrent chemoradiotherapy - Yen-Hao Chen; Hung-I Lu; Chien-Ming Lo; Yu-Ming Wang; Shang-Yu Chou; Chang-Chun Hsiao; Chao-Cheng Huang; Li-Hsueh Shih; Su-Wei Chen; Shau-Hsuan Li (BMC Cancer, 2018)
Abstract Background To evaluate the role of blood vascular endothelial growth factor (VEGF) kinetics in patients with locally advanced esophageal squamous cell carcinoma (ESCC) receiving curative concurrent chemoradiotherapy (CCRT). Methods A total of 97 locally advanced ESCC patients were enrolled. All the patients had their blood drawn at three time points to determine their levels of VEGF, including pre-chemotherapy (day 0), post-chemotherapy (day 5), and pre-cycle 2 chemotherapy (day 28). The VEGF levels were evaluated according to the day 0 value, day 5 value, day 28 value, day 5/day 0 ratio, day 28/day 0 ratio, and day 28/day 5 ratio. A VEGF cut-off level of 80 pg/mL was applied. Results In the analysis of progression-free survival (PFS), the patients less than 60 years old had significantly superior PFS compared to those more than 60 years old. Patients who had VEGF < 80 pg/mL at day 28 and a day 28/day 5 ratio < 1 had better PFS than those with VEGF > 80 pg/mL and a day 28/day 5 ratio > 1, respectively. In the analysis of overall survival (OS), patients with N0–1 status had significantly superior OS compared to those with N2–3 status. Furthermore, patients who had VEGF < 80 pg/mL at day 28, a day 5/day 0 ratio < 1, and a day 28/day 5 ratio < 1 had superior OS compared to those patients with VEGF > 80 pg/mL, a day 5/day 0 ratio > 1, and a day 28/day 5 ratio > 1, respectively. In the multivariate analysis, only VEGF < 80 pg/mL at day 28 and a day 28/day 5 ratio < 1 represented independent prognostic factors of superior PFS and OS. Conclusions Our study suggests that VEGF kinetics is a prognostic factor for locally advanced ESCC patients receiving curative CCRT. For these patients, lower post-treatment VEGF levels and decreasing levels of VEGF during CCRT are significantly associated with better clinical outcomes.